Acceleration of the numerical solution for the radiative transfer equation using a modified relaxation factor: X-factor method. Issue 5 (29th January 2020) - Torres-Aguilar, Carlos Enrique; Xamán, Jesús; Moreno-Bernal, Pedro; Hernández-Pérez, Iván; Zavala-Guillén, Ivett; Hernández-López, Irving Osiris
Abstract : Purpose: The purpose of this study is to propose a novel relaxation modified factor to accelerate the numerical solution of the radiative transfer equation (RTE) with several high-resolution total variation diminishing schemes. The methodology proposed is denoted as the X-factor method. Design/methodology/approach: The X-factor method was compared with the technique deferred-correction (DC) for the calculations of a two-dimensional cavity with absorting-emiting-scatteting gray media using the discrete ordinates method. Four parameters were considered to evaluate: the absorption coefficient, the emissivity of boundary surface, the scattering albedo and under-relaxation factor. Findings: The results showed the central processing unit (CPU) time of X-factor method was lower than DC. The reductions of CPU time with the X-factor method were observed from 0.6 to 75.4%. Originality/value: The superiority of the X-factor method over DC was showed with the reduction of CPU time of the numerical solution of RTE for evaluated cases.